2015
DOI: 10.1007/s00253-015-6900-y
|View full text |Cite
|
Sign up to set email alerts
|

The biostimulation of anaerobic digestion with (semi)conductive ferric oxides: their potential for enhanced biomethanation

Abstract: The effect of biostimulation with ferric oxides, semiconductive ferric oxyhydroxide, and conductive magnetite on the anaerobic digestion of dairy wastewater was examined in a batch mode. The reactors supplemented with ferric oxyhydroxide (R2) and magnetite (R3) showed significantly enhanced biomethanation performance compared with the control (R1). The removal of chemical oxygen demand (COD) after 30 days was 31.9, 59.3, and 82.5% in R1, R2, and R3, respectively. The consumed COD was almost fully recovered as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(76 citation statements)
references
References 49 publications
3
66
0
1
Order By: Relevance
“…Promoting DIET might enhance the anaerobic digestion of organic wastes, one of the few proven, effective, large-scale bioenergy strategies. Many studies have now shown that adding materials known to facilitate DIET either to anaerobic digesters, or methanogenic enrichment cultures metabolizing important intermediates in anaerobic digestion, can accelerate the rate of methane production; increase the methane content of the gas produced; and/or stabilize the digestion to permit higher organic loading rates (Viggi et al, 2014;Baek et al, 2015;Li et al, 2015a, b;Xu et al, 2015;Yamada et al, 2015;Zhao et al, 2015;Zhuang et al, 2015a, b;Beckmann et al, 2016;Lee et al, 2016). None of these studies have directly demonstrated DIET with detailed studies of microbial metabolism, but DIET was inferred from enrichment of microorganisms known to participate in DIET and/or increased rates of methane production.…”
Section: Harnessing Cell-to-cell Electrical Connections For Practicalmentioning
confidence: 99%
“…Promoting DIET might enhance the anaerobic digestion of organic wastes, one of the few proven, effective, large-scale bioenergy strategies. Many studies have now shown that adding materials known to facilitate DIET either to anaerobic digesters, or methanogenic enrichment cultures metabolizing important intermediates in anaerobic digestion, can accelerate the rate of methane production; increase the methane content of the gas produced; and/or stabilize the digestion to permit higher organic loading rates (Viggi et al, 2014;Baek et al, 2015;Li et al, 2015a, b;Xu et al, 2015;Yamada et al, 2015;Zhao et al, 2015;Zhuang et al, 2015a, b;Beckmann et al, 2016;Lee et al, 2016). None of these studies have directly demonstrated DIET with detailed studies of microbial metabolism, but DIET was inferred from enrichment of microorganisms known to participate in DIET and/or increased rates of methane production.…”
Section: Harnessing Cell-to-cell Electrical Connections For Practicalmentioning
confidence: 99%
“…Interestingly, it appears that conductive materials, including graphite particles (Kato et al ., ; Zhao et al ., ), granular activated carbon (Liu et al ., ; Rotaru et al ., ; Xu et al ., ; Dang et al ., ; Lee et al ., ), biochar (Chen et al ., ; Zhao et al ., ), graphene (Tian et al ., ), carbon nanotubes (CNT) (Li et al ., ; Zhang and Lu, ), carbon felt (Xu et al ., ) and carbon cloth (Chen et al ., ; Zhao et al ., ; Lei et al ., ), but also iron oxides as magnetite (Kato et al ., ; Cruz Viggi et al ., ; Baek et al ., ; Zhuang et al ., ; Yamada et al ., ; Tang et al ., ; Yang et al ., ; Yin et al ., ; Zhang and Lu, ; Jing et al ., ) may increase the rate of electron transfer and may affect metabolic pathways in anaerobic microbial processes by promoting DIET, between bacteria and methanogens. In general, these materials are highly stable, have large surface area, good adsorption capacity and high electric conductivity (Figueiredo et al ., ; Van der Zee and Cervantes, ; Pereira et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In both cases, it is likely that these iron oxides facilitated direct IET (electric syntrophy) between methanogens and electroactive iron-reducing bacteria, thus resulting in more acidogenic substrates (e.g. volatile fatty acids) for methanogenesis (Baek et al 2015;Ma et al 2015).…”
Section: Improvement Of Ad Performancementioning
confidence: 99%